Make me burn - Harte, Marie (Sourcebooks Casablanca, 2021)
"For reporter Avery Dearborn, not every on-camera moment is picture perfect. Take her latest interview: if a nimble passerby hadn't caught her, a leg-obsessed dog would have toppled her to the ground. To make matters worse, her helpful rescuer is none other than her archnemesis, hunky firefighter Brad Battle. Brad has served Seattle's residents for years, but he's never gone viral for it before. With the city melting over the hot new pair, Brad and Avery are forced to work together on a new livestreaming segment promoting pet adoptions... As anger turns to irresistible attraction, things heat up even more between Brad and Avery. But dodging their past is like playing with fire: if left unchecked, someone is sure to get burned."--Page 4 of cover.